POSTER AS A PROMOTIONAL MEDIA FOR COMPUTER COURSE PROGRAM OF LKP SCTC MRANGGEN DEMAK - Kusumaningrum, Dyah Ayu; Maulina, Rini (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Communication is one of the means of conveying information. LKP SCTC Mranggen Demak is a course and training institution that has been established since 2009. So far, the promotion carried out still relies on brochures. This research aims to analyze whether poster media is effective in increasing public interest and attention to computer courses at LKP SCTC Mranggen Demak, analyzing through poster visualization LKP SCTC Mranggen Demak, as a promotional media for computer courses. Data collection methods using literature and observation to find out what things are contained in the visual poster. The results showed that the poster still did not fulfill the elements of promotional objectives both verbal and non-verbal. The benefits of this research can be used by LKP SCTC in improving its promotional posters